KEBEBASAN BELAJAR DALAM KONSEP SUMMERHILL DAN KEBEBASAN BERPIKIR DALAM ISLAM: SUATU KAJIAN KOMPARATIF - Rizal, Zacky Al-Ghofir El-Muhtadi (Lembaga Penelitian Dan Pengabdian Masyarakat Stai Brebes, 2025)
This article explores in depth the concept of learning freedom in the Summerhill education system and the freedom of thought in Islamic teachings through a qualitative comparative approach. The purpose of this study is to critically analyze the similarities and differences between these two concepts within the framework of educational philosophy and character development. Summerhill, founded by A.S. Neill, emphasizes full freedom for students to determine their subjects, learning pace, and social participation, aiming to cultivate independence and personal responsibility through experiential learning. In contrast, Islam views freedom of thought as a divine right granted by God, yet it must remain within the boundaries of moral, spiritual, and ethical principles guided by divine revelation. The findings reveal that while both concepts promote autonomy and personal growth, their foundational frameworks differ—Summerhill adopts a humanistic-liberal orientation, whereas Islam upholds a theocentric and normative perspective. The significance of this study lies in its contribution to enriching modern educational discourse by integrating freedom and spiritual responsibility, offering theoretical insight for developing a balanced and humanistic-religious education model aligned with the Merdeka Belajar philosophy.